Brief in-play cooling breaks reduce thermal strain during football in hot conditions - Chalmers, S.; Siegler, J.; Lovell, R.; Lynch, G.; Gregson, W.; Marshall, P.; Jay, O. (Journal of Science and Medicine in Sport, 2019)
Objectives: The study examined if three feasible strategies involving additional in-play cooling periods attenuate the core (rectal) temperature rise during simulated football matches. Design: Four counterbalanced experimental trials in an environmental chamber set to 35°C ambient temperature, 55% relative humidity, and 30°C WBGT. Methods: Twelve healthy well-trained football players completed a regular simulated match (REG), regular simulated match with additional 3-min cooling periods at the 30-min mark of each half inclusive of chilled water consumption (COOLwater), regular simulated match with additional 3-min cooling periods at the 30-min mark of each half inclusive of chilled water consumption and the application of an ice towel around the neck (COOLtowel), regular simulated match with an extended (+5min; total of 20-min) half-time break (HTextended). Results: The difference in rectal temperature change was significantly lower in the COOLwater (-0.25°C), COOLtowel (-0.28°C), and HTextended (-0.21°C) trials in comparison to the REG (all p<0.05). Exercising heart rate and session rating of perceived exertion was lower in the COOLwater (-13bpm; -1.4au), COOLtowel (-10bpm; -1.3au), and HTextended (-8bpm; -0.9au) trials in comparison to the REG trial (all p<0.05). The cooling interventions did not significantly change skin temperature or thermal sensation in comparison to the REG (all p>0.05). Conclusions: All three cooling interventions attenuated core body thermal strain during simulated matches. The laboratory-based study supports the use of brief in-play cooling periods as a means to attenuate the rise in core temperature during matches in hot and humid conditions.